Isolation and identification of Epicoccum nigrum as the causal agent of brown spot disease in Solanum tuberosum in China. (10th January 2023) - Jin, Mengjun; Yang, Chengde; Wang, Yidan; Wei, Lijuan; Osei, Richard
Abstract: Brown spots occurring on potato leaves affect the normal growth of host plants. Recently, a new brown spot disease with some black dots was discovered on potato leaves in Dingxi, China. To confirm the causal agents of potato brown spots, the diseased lesions were collected and disinfected, and only one type of isolate, with football‐shaped conidia, was obtained from disinfected diseased leaves in three experimental fields. Pathogenicity tests of four representative isolates revealed that they can cause disease symptoms on 50%–75% of wounded and non‐wounded potato leaves. In addition, a typical isolate, DXPH, was identified based on morphological and molecular characteristics, and the colony and conidial characteristics were similar to those of Epicoccum sp . Multilocus sequence analysis showed that the internal transcribed spacer (ITS), RNA polymerase II second largest subunit ( RPB2 ) and β‐tubulin ( Tub2 ) genes of DXPH were 100%, 100% and 99% identical to the sequences of Epicoccum nigrum (CBS 140523), respectively. Additionally, antagonistic evaluation confirmed that the representative pathogenic strain DXPH showed greatest inhibition of the mycelial growth of Colletotrichum coccodes and Fusarium chlamydosporum in vitro, with antagonistic effects of 66.67% and 61.56%, respectively. Our findings provide evidence that E. nigrum can be pathogenic to potatoes in vivo in China, while retaining a biocontrol capacity on C. coccodes, Fusarium spp . and Botrytis cinerea in vitro, which will be helpful for the effective control of potato brown spot disease and management of the use of E. nigrum as a biological control agent. Abstract : This study presents the first report of the potato leaf spot caused by Epicoccum nigrum in China, which is also a biological control agent against several common pathogens in vitro, particularly Colletotrichum coccodes .